The Correlation Between Personality Types and Cerkak Writing Results in Grade X Students of SMA Negeri 1 Gombong - Yusuf Nur Kholiq; Joko Sukoyo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
Student personality types are thought to have a correlation with the results of writing cerkak. This study aimed to determine the correlation between personality types and the results of writing cerkak in grade X students at SMA Negeri 1 Gombong. This study used a correlational research design with a sample of 35 students. Data collection techniques used were observation techniques, interviews, and tests. Data analysis was performed using regression and correlation. The results showed that personality types and cerkak writing results strongly correlated with a coefficient of 0.874. Students with introverted personality types had better results than extroverted students